Determination of Gravitational Acceleration Using the Concept of Free Fall Motion - Wibowo, Rifky Tri; Kolo, Maria Jennifer Del Amore; Rahma, Anisa Nur; Kurniawati, Wahyu (Sean Institute, 2024)
This research discusses the method of determining gravitational acceleration through the concept of free fall motion. Using a theoretical approach, this research explains the basic principles of free fall motion proposed by Galileo Galilei and Isaac Newton. Through measuring the time of a free object falling from a certain height. Data analysis describes the relationship between fall time and distance, providing results that accurately approximate the value of Earth's gravitational acceleration. The conclusion of this article contributes to the understanding of basic physics concepts, as well as providing a practical method for determining gravitational acceleration using the principles of free fall motion.